Survey of the demand for care services for older people and the training needs of their care workers: a cross-sectional study in Northeast China - Shuqin Li; Jun Zhang; Yan Liu; Ai-ping Wang; Guixing Qiu (BMC, 2022)
Abstract Background The older population is increasingly utilizing professional healthcare services, while the requirements for caregivers are becoming more demanding. Therefore, it is important to be mindful not only of the service needs of older people but also to consider the training needs of their care workers. The present study aimed to investigate the care service needs for older people and the training needs of their care workers. Methods A cross-sectional questionnaire was used to survey 589 residents of 6 nursing homes and 2 geriatric hospitals, 415 medical staff from 7 geriatric hospitals, 5 nursing homes, and 1 community institution, and 372 nursing assistants from 21 nursing institutions in northeast China. Results The service with the greatest demand and that with which users were most satisfied was regular visits by healthcare personnel, which was the case for 87.27% of the care recipients. Of the medical staff, 75.42% had training needs related to geriatric healthcare, while the most requested training content was the comprehensive assessment of old people. The most requested method for the delivery of training was by self-study online video courses. Of nursing assistants, only 53.4% had obtained the relevant practicing certificate. While 83.6% participated in relevant training, 86% expressed the need for additional training. The majority of this category of staff wished to receive training in everyday care routines, and the majority wanted to learn by way of practical training. Conclusions The care needs of the older population are diverse, and the work performed by healthcare personnel is increasing in scope. The existing training system for such care personnel is not perfect, and the demand for training is high. Existing training methods and content require improvement.